EMPRESS: A Pan-European Project to Enhance Manufacturing Process Efficiency through Improved Temperature Control. (October 2016) - Pearce, Jonathan
A pan-European project aimed at enhancing process efficiency through improved temperature measurement (EMPRESS) is described. The project is aimed at solving a suite of specific, documented problems in high-value manufacturing industry through improved temperature metrology for process control. A key aspect is the introduction of traceability to the International Temperature Scale of 1990 in process. This involves a concerted effort across Europe to improve existing sensing techniques such as thermocouples and fibre-optic based pyrometry, as well as introduction of completely new techniques including phosphor thermometry and combustion thermometry. Each activity in the project is characterised by the involvement of an end-user in industry, and there are opportunities for joining the Stakeholder Community associated with the project.